Relationship Between Energy Prices, Monetary Policy and Inflation; A Case Study of South Asian Economies - Atiq-ur-Rehman (Journal of Central Banking Theory and Practice, 2014)
Monetary policy tools, including money supply and interest rate, are the most popular instruments to control inflation around the globe. It is assumed that a tight monetary policy, either in form of reduction in money supply or an increase in interest rate, will reduce inflation by reducing aggregate demand in an economy. However, monetary policy could be counterproductive if cost side effects of monetary tightening prevail. High energy prices may increase the cost of production by reducing aggregate supply in the economy. If tight monetary policy is used to reduce this cost push inflation, the cost side effect of energy prices will add to cost side effects of monetary tightening and will become dominant. In this case, the monetary policy could be counterproductive. Furthermore, simultaneous reduction in aggregate supply and aggregate demand will bring twofold reduction in output. Therefore greater care is needed in the use of monetary policy in the situation of cost push inflation. This article investigates the presence of cost side effect of monetary transmission mechanism, the role of international oil prices in domestic inflation, and implications for monetary policy. The findings suggest that both monetary policy and oil prices have cost side effects on inflation and monetary tightening could be counterproductive if used to reduce energy pushed inflationary trend.
Keywords: E50; E52; E58; 330; Oil Price; Inflation; Monetary Policy; Cost Channel; Demand Channel